Pengaruh Perputaran Kas, Perputaran Piutang, Dan Perputaran Persediaan Terhadap Profitabilitas Perusahaan - Puspitasari, Ratih; Yolanti, Tiara Novita (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
Cash turn over, accounts receivable turn over, and inventory turn over have a strong. Three components capital work can be managed in defferent ways to maximize profitability or to improve the growth in the company. The purpose of this study was to determine the influence of cash turnover on profitability of the company, how the receivables tunover on the profitability of the company, how the inventory turnover on the profitability of the company, how the cash turnover and account receivable turnover on the profitability of the company, how the cash turnover and inventory turnover on the profitability of the company, how the account receivable turnover and inventory turnover on the profitability of the company, how the cash turnover, account receivable turnover, and inventory turnover on the profitability at the company PT. Mayora Indah, Tbk, PT. Ultrajaya Milk Industry, Tbk, and PT. Delta jakarta, Tbk years 2010-2014. The method used is descriptive study, ratio analysis, and statical analysis. Based on the result of research can be concluded that the PT. Mayora Indah, Tbk, PT. Ultrajaya Milk Industry, Tbk, and PT. Delta jakarta, Tbk cash turnover has a negative and significant effect on profitability of the company, account receivable turnover has a positive and significant impact on profitability of the company, inventory turnover has a positive and significant effect on profitability of the company, cash turnover and account receivable turnover that cash turnover has a negative and significant effect on profitability of the company and account receivable has a positive and significant impact on profitability of the company, cash turnover and inventory turnover that cash turnover has a negative and significant effect on profitability of the company and inventory turnover has a positive and significant effect on profitability of the company, account receivable turnover and inventory turnover that account receivable turnover has a positive and significant impact on profitability of the company and inventory turnover has a positive and significant effect on profitability of the company, and cash turnover, account receivable turnover, and inventory turnover simultaneously no significant effect on profitability.